2023
DOI: 10.1007/s40732-023-00537-1
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Stability among Delay, Probability, and Effort Discounting in Humans

Abstract: The stability of delay discounting across time has been well-established. However, limited research has examined the stability of probability discounting, and no studies of the stability of effort discounting are available. The present study assessed the steady-state characteristics of delay, probability, and effort discounting tasks across time with hypothetical rewards in humans, as well as whether response characteristics suggested a common discounting equation. Participants completed delay, probability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…We excluded articles if they involved reliability measures that were collected before and after an intervention or treatment context (given the suspected influence such interventions would have on captured test–retest reliability). Any discounting process was eligible for inclusion; however, only delay‐ and probability‐discounting studies were identified in more than one manuscript, allowing for meta‐analytic comparisons (one article, Escobar et al, 2023, evaluated effort‐discounting reliability in addition to delay and probability, but effort‐discounting reliability was not evaluated elsewhere). Figure 1 depicts the search and refinement process as outlined by PRISMA guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded articles if they involved reliability measures that were collected before and after an intervention or treatment context (given the suspected influence such interventions would have on captured test–retest reliability). Any discounting process was eligible for inclusion; however, only delay‐ and probability‐discounting studies were identified in more than one manuscript, allowing for meta‐analytic comparisons (one article, Escobar et al, 2023, evaluated effort‐discounting reliability in addition to delay and probability, but effort‐discounting reliability was not evaluated elsewhere). Figure 1 depicts the search and refinement process as outlined by PRISMA guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Para evaluar el DT comúnmente se presentan recompensas en pares de opciones que se entregan de inmediato o en un tiempo determinado en el futuro (Miller, Reed y Amlung, 2023), dichas recompensas pueden ser reales, potencialmente reales o hipotéticas (Scholten et al, 2019) y su objetivo es encontrar el punto de indiferencia o valor subjetivo, es decir el cambio de punto de elección del valor inmediato al retardado o viceversa (Miller et al, 2023). Con estos puntos de indiferencia se genera una curva con valores subjetivos para cada participante y se calcula una tasa de descuento que refleja el grado de impulsividad de quien resuelve la tarea (Escobar et al, 2023).…”
Section: Introductionunclassified
“…Risk preferences (i.e., the tendency to choose larger risky versus smaller certain rewards) and intertemporal preferences (i.e., the tendency to choose larger later versus smaller sooner rewards) are two moderately stable individual differences (Chuang & Schechter, 2015;Escobar et al, 2023;Hertwig et al, 2019;Mata et al, 2018;Meier & Sprenger, 2015;Seneca et al, 2012;Zeynep Enkavi et al, 2019) linked to important outcomes in life. Risk preferences have been associated with heavy drinking, smoking, being overweight/obese, seat belt non-use, not having insurance, holding stocks instead of treasury bills (Anderson & Mellor, 2008;Barsky et al, 1997;Lejuez et al, 2003Lejuez et al, , 2005; self-employment status (Ekelund et al, 2005), pathological gambling (Branas-Garza et al, 2007;Wiehler & Peters, 2015), and financial decisions (Noussair et al, 2014).…”
mentioning
confidence: 99%